2017
DOI: 10.1016/j.fsigen.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Trace DNA evidence dynamics: An investigation into the deposition and persistence of directly- and indirectly-transferred DNA on regularly-used knives

Abstract: Empirical data on the transfer and persistence of trace DNA are crucial to the evaluation of forensic DNA evidence. This evaluation can be complicated by the occurrence of indirect DNA transfer; the possibility of which is well established, but research into such transfer is often focussed on unrealistic situations, e.g. handling of DNA-free items after participants have shaken hands for 1-2min. To simulate more realistic scenarios, this study investigated the deposition and persistence of both directly- and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 28 publications
7
46
1
Order By: Relevance
“…Profile interpretation showed that whilst in most of samples the office owner was the only or the major/majority contributor to the samples, the temporary occupier was detected as a major/majority contributor on several items in both laboratories, despite the relatively shorter duration of use ( Table 2). Detection of the last person temporarily touching or using an item or space, in differing degrees relative to the previous handler/owner, concurs with findings of previous studies [8][9][10][11][12][13][14]. Several of the samples where the temporary occupier was a major/majority contributor were from relatively small surface areas, suggesting that with prolonged use, the DNA of the owner may be more readily removed and replaced with the DNA of the temporary occupier.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Profile interpretation showed that whilst in most of samples the office owner was the only or the major/majority contributor to the samples, the temporary occupier was detected as a major/majority contributor on several items in both laboratories, despite the relatively shorter duration of use ( Table 2). Detection of the last person temporarily touching or using an item or space, in differing degrees relative to the previous handler/owner, concurs with findings of previous studies [8][9][10][11][12][13][14]. Several of the samples where the temporary occupier was a major/majority contributor were from relatively small surface areas, suggesting that with prolonged use, the DNA of the owner may be more readily removed and replaced with the DNA of the temporary occupier.…”
Section: Discussionsupporting
confidence: 86%
“…While the DNA proportions of the last user and the owner of the item (if the last user and the owner are two different people) has been investigated for commonly used items [8][9][10][11][12][13][14], there are a number of other scenarios that require further investigation. A common scenario where this may be relevant involves a person (or a few people) temporarily occupying a space known to be predominantly occupied by a single person (or a few people), in the absence of the original occupant (s) e.g.…”
Section: Introductionmentioning
confidence: 99%
“…DNA from person A residing on the hand of person B is then transferred to object 1 when contacted by person B with bare hands. DNA from person A is detected on object 1 [51][52][53][54]. -DNA residing on a specific area of a collected item (object 1), that has been packaged along with a second item (object 2) in the same packaging, is transferred to another area of object 1, to another item (object 2), or to the inside of the packaging [55].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…a sunlit windowsill) has been shown to lower this persistence significantly, with recovered DNA displaying clear degradation in typing results after 2 weeks [51]. Total DNA recovered from knives immediately after use compared to a week later, was reported to be significantly higher in only 50% of subjects [53]. There is limited systematic investigation of the time course of DNA degradation, particularly in either casework-like touch deposit samples or over significant amounts of time.…”
Section: Persistence and Interactions Of Trace Dna In Its Environmentmentioning
confidence: 99%